Pengaruh Brand Ambassador dan Brand Image terhadap Keputusan Pembelian Produk Scarlett Whitening - Wahyudi Wahyudi; Amir Hamzah; Hasanatul Rahmaniah (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to determine the simultaneous and partial influence and dominant variables of brand ambassador (X1) and brand image (X2) on the Purchase Decision (Y) of Scarlett Whitening Products. The research design used in this study is a quantitative research design. The population in this study were all active students of STIE Widya Praja Tanah Grogot from semester two to semester eight who used Scarlett Whitening products as many as 50 people. The sampling technique in this study used a nonprobability sampling technique with a saturated sampling type, so that in this study the number of samples taken was 50 respondents. The data analysis technique used was multiple linear regression analysis using the assistance of SPSS. The calculation result of the brand image variable (X2) obtained a t-value of 2.186 and a significant level of 0.034 when compared to the t-table value of 2.01174 (t-count> t-table) or 2.186> 2.01174 with a significant level of 0.034> 0.05 which means H0 is rejected and Ha is accepted, so it can be concluded that the brand image variable (X2) has a significant influence on the decision to purchase Scarlett Whitening products among students of the Widya Praja Tanah Grogot School of Economics. Of the two independent variables studied, it is known that the brand ambassador variable (X1) is the variable that has the dominant influence on purchasing decisions, this is evidenced by the results of t-count> t-table (3.752> 1.67793) with a significant value of 0.000 <0.05.